Dancing with the pygmy elephant: The Canadian space program, future directions amid challenges. (November 2017) - Handberg, Roger
Abstract: Since the inception of the space age, Canada has pursued a partnership with the U.S. through NASA including participation from the Apollo era forward to the International Space Station. Canada joined the European Space Agency as a participating state since 1979. While these cooperative activities continued over the years, Canada also carved out areas of technology that both created economic returns but were valuable in terms of the joint projects. In a change that impacts Canada, NASA began restructuring its mission profile while it grappled with the shuttle program's termination and a downturn in the national economy. For Canada, finding a way forward for its space program is essential given the economic benefits and the international cache that accrues to a middle sized state that operates an independent space program. Finding its way forward is not easy given the costs associated with such endeavors. This paper examines Canada's current program development and its direction given the U.S. decline relative to other space powers. It also places Canada's program in the context of the debate over space technology utilization for economic development and competitiveness. Highlights: Examination of US-Canadian space relationship in a period of change. Discussion of Canada's strategic options regarding space activities. Illustrates impact of US relative decline in space activities due to a lack of focus. Examination of the growing impact of commercial space activities on Canadian and by extension US space activities. Illustration of how a middle state navigates an increasing complex international space environment.